Intensity‐Enhanced Apodization Effect on an Axially Illuminated Circular‐Column Particle‐Lens. Issue 2 (27th December 2017) - Yue, Liyang; Yan, Bing; Monks, James N.; Dhama, Rakesh; Wang, Zengbo; Minin, Oleg V.; Minin, Igor V.
Abstract: A particle can function as a refractive lens to focus a plane wave, generating a narrow, high intensive, weak‐diverging beam within a sub‐wavelength volume, known as the 'photonic nanojet'. It is known that apodization method, in the form of an amplitude pupil‐mask centrally situated on a particle‐lens, can further reduce the waist of a photonic nanojet, however, it usually lowers the intensity at the focus due to blocking the incident light. In this paper, the anomalously intensity‐enhanced apodization effect was discovered for the first time via numerical simulation of focusing of the axially illuminated circular‐column particle‐lenses, and a greater than 100% peak intensity increase was realised for the produced photonic nanojets. Abstract : The anomalously intensity‐enhanced apodization effect was discovered for the first time via numerical simulation of focusing of the axially illuminated circular‐column particle‐lenses, and a greater than 100% peak intensity increase can be realised for the produced photonic nanojets due to convergence of power flows and analogy of increase of effective refractive index for the particle‐lens material.